Structure-activity relationships of benzothiazole GPR35 antagonists. Issue 3 (1st February 2017) - Abdalhameed, Manahil M.; Zhao, Pingwei; Hurst, Dow P.; Reggio, Patricia H.; Abood, Mary E.; Croatt, Mitchell P.
Graphical abstract: Abstract: The first structure-activity relationships for a benzothiazole scaffold acting as an antagonist at GPR35 is presented. Analogues were designed based on a lead compound that was previously determined to have selective activity as a GPR35 antagonist. The synthetic route was modular in nature to independently explore the role of the middle and both ends of the scaffold. The activities of the analogues illustrate the importance of all three segments of the compound.